2006
DOI: 10.2166/wst.2006.194
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic acid removal by acrylic acid utilizing bacteria from acrylonitrile–butadiene–styrene resin manufactured wastewater treatment system

Abstract: The aim of this study is to isolate the acrylic acid utilizing bacteria from the ABS resin manufactured wastewater treatment system. The bacteria should have the ability to remove acrylic acid and tolerate the acrylonitrile and acrylamide toxicity. The aim is also to understand the performance of isolated pure strain for treating different initial acrylic acid concentrations from synthetic wastewater. The results are: twenty strains were isolated from the ABS resin manufactured wastewater treatment system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…To date, only three studies have isolated bacteria involved in the metabolism of acrylic acid (2,24,71), highlighting a lack of knowledge in this area. The isolates derived from our coral samples were related to Photobacterium, Halomonas, and Shewanella spp., as well as to several Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only three studies have isolated bacteria involved in the metabolism of acrylic acid (2,24,71), highlighting a lack of knowledge in this area. The isolates derived from our coral samples were related to Photobacterium, Halomonas, and Shewanella spp., as well as to several Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Another study ) evaluated the effect of HRT on a similar system. Wang and Lee (2006) by high resolution GC-MS. Calibration curves and method detection limits obtained for these solvents using the two SPME fibres confirmed that the 100-PDMS fibre provided better sensitivity, but the saturation was reached at a lower concentration than 85-PA fibre. Lu et al (2006) carried out an analysis of chemical compositions that may contribute to the COD of oilfield produced water treatment system.…”
Section: Wastewatermentioning
confidence: 99%